2014
DOI: 10.1111/hae.12512
|View full text |Cite
|
Sign up to set email alerts
|

Falling and fall risk factors in adults with haemophilia: an exploratory study

Abstract: Falls are a particular risk in persons with haemophilia (PWH) because of damaged joints, high risk of bleeding, possible impact on the musculoskeletal system and functioning and costs associated with treatment for these fall-related injuries. In addition, fall risk increases with age and PWH are increasingly entering the over 65 age group. The aim of this study was to determine the occurrence of falls during the past year and to explore which fall risk factors are present in community-dwelling PWH. Dutch speak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Prior research has established that falls are commonplace in adults with hemophilia,1, 2 and advises that physical therapy and exercise are successful in fall prevention 3, 4. Limited exercise and physical activity leads to a decline in balance, increasing fall risk 5.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has established that falls are commonplace in adults with hemophilia,1, 2 and advises that physical therapy and exercise are successful in fall prevention 3, 4. Limited exercise and physical activity leads to a decline in balance, increasing fall risk 5.…”
Section: Introductionmentioning
confidence: 99%
“…Others have reported an even higher prevalence (50% in the preceding 12 months compared with 10% in age-matched controls) [22]. Risk factors associated with falls are living conditions, physical activity, avoidance of winter sports, urinary incontinence and decreased mobility [21], as well as common factors reported in the general population, such as a history of a previous fall, orthopaedic status (including arthritis and decreased strength in lower extremities and reduced hip extension range), pain with daily activities, avoidance of pain-related exercise, depression and HIV infection [23]. Haemophilic arthropathy and acute musculoskeletal bleeding as a consequence of a fall, and subsequent behaviour, further increase the risk of re-falling, creating, thus, a vicious cycle [4].…”
Section: Epidemiological Data On Fracture Riskmentioning
confidence: 99%
“…Indeed, a recent study reported that about one-third of patients with severe or moderate haemophilia A or B experience at least one fall per year, 42% of which more than once (with an average of four falls) [21]. Others have reported an even higher prevalence (50% in the preceding 12 months compared with 10% in age-matched controls) [22].…”
Section: Epidemiological Data On Fracture Riskmentioning
confidence: 99%
“…An ongoing study has suggested both physical therapy and occupational therapy programs in older patients with hemophilia are feasible, and would be reasonable options for patients with VWD 115. An interesting study in hemophilia patients indicated overall a reduced risk of falls, presumably because of an increased level of caution when ambulating and avoidance of fall risks 116. More studies on the risk and management of osteoporosis and falls in elderly VWD patients are needed.…”
Section: Vwd and Osteoporosis Fracture Risk And Fallsmentioning
confidence: 99%